The Influence of Information Technology on Managerial Performance: Management Accounting Systems As Intervening Variables - Puspita Maelani; Najmudin Najmudin (Jurnal Riset Akuntansi Terpadu, 2023)
The purpose of this study was to determine and analyze the influence of information technology on managerial performance mediated by the management accounting system. The method used in this study is descriptive quantitative, with a population of Manufacturing SMEs in Serang Regency, sampling using a purposive sampling technique, The data in this study were obtained by sending questionnaires directly to the respondents. The data that has been obtained is analyzed using the structural equation modeling (SEM) method with the partial least squares (PLS) approach. The results of this study indicate that information technology has a positive and significant effect on the managerial performance of Small and Medium Enterprises (SMEs), information technology has a positive and significant effect on SME management accounting systems, management accounting systems has a positive and significant effect on SME managerial performance, and information technology has a significant and positive effect on SME managerial performance. indirectly on the managerial performance of SMEs through the management accounting system. The implications of this study are the use of information technology on managerial performance in SMEs so that they can obtain information related to the management accounting system needed by SMEs in making decisions.